Density Effect on Flame Retardancy, Thermal Degradation, and Combustibility of Rigid Polyurethane Foam Modified by Expandable Graphite or Ammonium Polyphosphate - Hongyu Yang (Polymers, 2019)
The current study aims at comparatively investigating the effect of apparent density on flame retardancy, thermal degradation and combustion behaviors of rigid polyurethane foam (RPUF), RPUF/ expandable graphite (EG) and RPUF/ ammonium polyphosphate (APP). A series of RPUF, RPUF/EG and RPUF/APP samples with different apparent densities (30, 60 and 90 kg/m3) were prepared. The flame retardancy, thermal degradation, and combustion behaviors of each sample were investigated. Limiting oxygen index (LOI) results indicated that increasing apparent density was beneficial to the flame retardancy of all foam systems. The effect of apparent density on the enhancement of flame retardancy followed the sequence of RPUF < RPUF/APP < RPUF/EG. Thermogravimetric analysis (TGA) results showed that an increase in the apparent density can cause more weight loss in the first degradation stage and less weight loss in the second degradation stage for all foam systems. The combustion behaviors also showed significant differences. The samples with a higher apparent density showed a longer duration of heat release and higher total heat release (THR). The findings in this study demonstrated that apparent density played an important role in flame retardancy, thermal degradation, and combustion behaviors of RPUF, which must be paid more attention in the studies of flame-retardant RPUF.